(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
Initially designed at the end of the 18th century to identify the exact location of a fire during the dark hours of the night, the toposcope became in the following decades a tourist attraction device. Thanks most of all to the work of Alpine and Touring Clubs, the presence of these instruments spread throughout Europe under many names (Toposkop, Indicateur des Alpes, Table d’orientation). Alpine regions have been their crib, but they rapidly reached other environments. Wherever there was a good 360° vision of the surroundings, a toposcope could be placed. They constitute a universe that is as connected as varied. The deep time of their technology and their applicative variations also testify a migratory path which resembles many other panoramic devices. The article aims therefore to media-archaeologically trace the major dynamics of the toposcope. Not to uniform them under a homogeneous history, but to reflect upon its role in defining the modern meanings of mobility and virtuality. In that, the toposcope represents an interesting point of view since, unlike many other panoramic devices, it provides for an in situ mediated experience. Sharing some features with Augmented Reality, the toposcope elaborates a different approach to optical immersive experience.